Taxonomic revision of the Protopolybia sedula species-group (Hymenoptera, Vespidae, Polistinae), with an new identification key to species - Dos Santos, José N. A. Junior; Silveira, Orlando T.; Carpenter, James M. (Zootaxa, 2018)
A taxonomic review of the P. sedula species-group is presented. New diagnostic characters are described and all species redescribed. The male genitalia of P. sedula (de Saussure) and P. weyrauchi Bequaert are described and drawn. New collection records and a new identification key for the species-group are given.